Adsorbing material as well as preparation method and application thereof

The adsorbent material prepared by combining a cerium-doped metal organic frame with carbon nanotubes solves the problems of environmental pollution, high cost and low efficiency in the existing arsenic removal technology, and achieves an efficient and economical groundwater arsenic removal effect.

CN119793401APending Publication Date: 2025-04-11NINGXIA UNIVERSITY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510145137.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-10
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

The existing arsenic removal technology has problems of environmental pollution, high cost and low efficiency, especially the difficulties in large-scale promotion and application of precipitation and membrane separation.

Method used

A highly efficient adsorption material was prepared by combining the cerium-doped metal organic frame with the carbon nanotubes and calcining it. This material combines the carbon framework structure of the metal-organic frame with the high porosity and large specific surface area of ​​the carbon nanotubes, significantly improving the ability to capture arsenic.

Benefits of technology

It has achieved efficient removal of arsenic in groundwater, with an arsenic removal rate of 98.3%. Due to the high regeneration ability and chemical stability of the material, the risk of environmental pollution and treatment costs are reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
  • Figure SMS_4
    Figure SMS_4
Patent Text Reader

Abstract

The invention relates to the technical field of underground water treatment, in particular to an adsorbing material as well as a preparation method and application thereof. The invention provides a preparation method of an adsorption material, which comprises the following steps: mixing an organic ligand, a soluble iron salt, a soluble cerium salt and a first organic solvent for the first time, adding glacial acetic acid, and carrying out a first solvothermal reaction to obtain a cerium-doped metal organic framework; performing second mixing on the cerium-doped metal organic framework, a carbon nanotube and a second organic solvent, and performing second solvothermal reaction to obtain a carbon nanotube and cerium-doped metal organic framework compound; and calcining the carbon nano tube and cerium doped metal organic framework compound to obtain the adsorption material. The adsorbing material prepared by the preparation method disclosed by the invention has excellent arsenic removal rate.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of groundwater treatment, and in particular to an adsorption material and a preparation method and application thereof. Background Art

[0003] At present, commonly used arsenic removal technologies include precipitation, ion exchange, membrane separation and adsorption. Among them, precipitation can be divided into flocculation precipitation and electrocoagulation. The use of the above two methods will lead to the generation of a large amount of sediment, which often needs to be treated by landfill, which may cause secondary pollution to the environment. The ion exchange method is simple to operate, has good results, and has strong regeneration ability, but it has strict requirements on water quality and requires As(III) to be oxidized to As(V) in advance, which increases the purification process and components. The membrane separation method is suitable for water systems with small processing volumes, but due to the high cost of membrane devices and the need for timely cleaning and scraping of ultrafiltration membranes, it cannot be widely promoted and applied. Therefore, the adsorption method is currently one of the most effective arsenic removal methods, with a removal rate of about 90% to 98%. The development of efficient adsorbents is the key to arsenic removal by adsorption. Summary of the invention

[0004] In view of this, the object of the present invention is to provide an adsorption material and a preparation method and application thereof. The adsorption material prepared by the preparation method of the present invention has an excellent arsenic removal rate.

[0005] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0006] The present invention provides a method for preparing an adsorbent material, comprising the following steps:

[0007] After first mixing the organic ligand, the soluble iron salt, the soluble cerium salt and the first organic solvent, glacial acetic acid is added to perform a first solvothermal reaction to obtain a cerium-doped metal organic framework;

[0008] After a second mixing of the cerium-doped metal organic framework, the carbon nanotubes and the second organic solvent, a second solvothermal reaction is performed to obtain a carbon nanotube and cerium-doped metal organic framework composite;

[0009] The carbon nanotube and cerium-doped metal organic framework composite are calcined to obtain the adsorption material.

[0010] Preferably, the organic ligand includes one or more of trimesic acid, terephthalic acid and 2-aminoterephthalic acid.

[0011] Preferably, the molar ratio of the organic ligand, the iron in the soluble iron salt and the cerium in the soluble cerium salt is (2-4):1:1.

[0012] Preferably, the temperature of the first solvent thermal reaction is 80 to 250° C., and the time is 12 to 72 hours.

[0013] Preferably, after the first solvent thermal reaction is completed, cooling, centrifugation, washing and drying are further performed in sequence.

[0014] Preferably, the mass ratio of the cerium-doped metal organic framework to the carbon nanotubes is (5-15):1.

[0015] Preferably, the temperature of the second solvent thermal reaction is 70-200° C., and the time is 12-72 hours.

[0016] Preferably, the calcination is carried out in a protective atmosphere;

[0017] The calcination temperature is 250-600° C., the heating rate is 2-10° C. / min, and the heat preservation time is 4-10 hours.

[0018] The present invention also provides an adsorption material prepared by the preparation method described in the above technical solution, comprising carbon nanotubes and a bimetallic center oxide material centered on iron and cerium loaded in the carbon nanotubes.

[0019] The present invention also provides application of the adsorption material described in the above technical solution in the field of arsenic removal from groundwater.

[0020] The present invention provides a method for preparing an adsorbent material, comprising the following steps: first mixing an organic ligand, a soluble iron salt, a soluble cerium salt and a first organic solvent, adding glacial acetic acid, and performing a first solvothermal reaction to obtain a cerium-doped metal organic framework; second mixing the cerium-doped metal organic framework, carbon nanotubes and a second organic solvent, and performing a second solvothermal reaction to obtain a carbon nanotube-cerium-doped metal organic framework composite; and calcining the carbon nanotube-cerium-doped metal organic framework composite to obtain the adsorbent material. The preparation method of the present invention synthesizes the adsorbent material by combining the cerium-doped metal organic framework with the carbon nanotubes and then calcining them. The adsorbent material can inherit the carbon skeleton structure of the metal organic framework, has a larger specific surface area and more active sites, and significantly improves its arsenic capture ability; the carbon nanotubes have high porosity and large specific surface area, and after combining with the bimetallic center oxide material formed after calcination, the specific surface area and pore structure of the adsorbent material are further increased, thereby improving its adsorption capacity and efficiency. In addition, the bimetallic center oxide material provides multiple types of adsorption sites, which can effectively bind arsenic of different valence states (such as As(III) and As(V)), thereby improving the adsorption efficiency. According to the records of the examples, the arsenic removal rate of the adsorbent material prepared by the preparation method of the present invention reaches 98.3%.

[0021] Compared with the prior art, the present invention has the following beneficial effects:

[0022] 1) The cerium-doped metal organic framework of the present invention has a stable carbon skeleton pore structure. After calcination, it can expose more metal adsorption sites while maintaining the original carbon skeleton structure. At the same time, carbon nanotubes have a high specific surface area and porous structure. Therefore, carbon nanotubes provide more active sites for the metal organic framework and further increase the conductivity of the adsorption material. Compared with the existing technology, the adsorption capacity of arsenic can be greatly enhanced, and the pores can also be adjusted to selectively adsorb arsenic.

[0023] 2) The addition of carbon nanotubes can also improve the chemical stability of the adsorption material, making the adsorption material more durable in practical applications. The introduction of carbon nanotubes helps to improve the regeneration ability of the adsorption material, making it easier to desorb and regenerate after adsorption, and enhancing the reusability. Compared with the existing technology, the adsorption material can improve the adsorption kinetics, accelerate the rate of arsenic adsorption, and improve the treatment efficiency;

[0024] 3) The cerium element can change the electronic structure of the metal center of the cerium-doped metal organic framework, enhance the interaction between iron and arsenic, and thus improve the adsorption selectivity and capacity; the porous structure of the carbon nanotubes helps to quickly release the adsorbed arsenic during the desorption process, making the prepared adsorption material easier to regenerate and recycle, reducing costs and improving economic benefits. The adsorption material strongly binds to arsenic ions through chemical adsorption, while the carbon nanotubes provide assistance through physical adsorption. The combination of the two makes the adsorption more efficient and stable.

[0025] The present invention also provides the use of the adsorption material described in the above technical solution in the field of arsenic removal from groundwater. The adsorption material described in the present invention can efficiently remove arsenic from groundwater by adsorption, and compared with the traditional chemical precipitation method, it does not produce a large amount of solid waste, thereby reducing the difficulty and cost of waste treatment; at the same time, the adsorbed arsenic can be recovered by a simple desorption process, thereby realizing the reuse of the adsorbent and the recovery of resources, reducing the risk of environmental pollution, and improving the treatment efficiency and economic benefits. DETAILED DESCRIPTION

[0026] The present invention provides a method for preparing an adsorbent material, comprising the following steps:

[0027] After first mixing the organic ligand, the soluble iron salt, the soluble cerium salt and the first organic solvent, glacial acetic acid is added to perform a first solvothermal reaction to obtain a cerium-doped metal organic framework (denoted as Fe / Ce-MOF);

[0028] The cerium-doped metal organic framework, carbon nanotubes and a second organic solvent are mixed for a second time, and then subjected to a second solvothermal reaction to obtain a carbon nanotube and cerium-doped metal organic framework composite (denoted as CNT-Fe / Ce-MOF);

[0029] The carbon nanotube and cerium-doped metal organic framework composite are calcined to obtain the adsorption material (denoted as CNT-Fe / Ce-MOF / NC).

[0030] In the present invention, unless otherwise specified, all preparation raw materials are commercially available products well known to those skilled in the art.

[0031] The invention comprises the following steps: firstly mixing an organic ligand, a soluble iron salt, a soluble cerium salt and a first organic solvent, adding glacial acetic acid, and performing a first solvent thermal reaction to obtain a cerium-doped metal organic framework.

[0032] In the present invention, the organic ligand preferably includes one or more of trimesic acid, terephthalic acid and 2-aminoterephthalic acid, and more preferably includes trimesic acid; when the organic ligand is two or more of the above specific selections, the present invention has no special restrictions on the ratio of the above specific substances, and they can be mixed in any ratio. In an embodiment of the present invention, the organic ligand can be trimesic acid.

[0033] In the present invention, the soluble iron salt preferably includes one or more of ferric chloride hexahydrate, ferric citrate, ferric sulfate and ferric nitrate, and more preferably ferric chloride hexahydrate; when the soluble iron salt is two or more of the above specific selections, the present invention does not have any special restrictions on the ratio of the above specific substances, and they can be mixed in any ratio. In an embodiment of the present invention, the soluble iron salt can be ferric chloride hexahydrate.

[0034] In the present invention, the soluble cerium salt preferably includes one or more of cerium nitrate hexahydrate, cerium chloride and cerium acetate, and more preferably cerium nitrate hexahydrate; when the soluble cerium salt is two or more of the above specific selections, the present invention has no special restrictions on the ratio of the above specific substances, and they can be mixed in any ratio. In an embodiment of the present invention, the soluble cerium salt can be cerium nitrate hexahydrate.

[0035] In the present invention, the first organic solvent preferably includes one or more of N,N-dimethylformamide (DMF), dimethyl sulfoxide, acetonitrile and anhydrous ethanol. When the first organic solvent is two or more of the above specific selections, the present invention has no special restrictions on the ratio of the above specific substances, and they can be mixed in any ratio. In an embodiment of the present invention, the first organic solvent can be DMF.

[0036] In the present invention, the molar ratio of the organic ligand, the iron in the soluble iron salt and the cerium in the soluble cerium salt is preferably (2-4): 1: 1, more preferably 3: 1: 1. In an embodiment of the present invention, the molar ratio of the organic ligand, the iron in the soluble iron salt and the cerium in the soluble cerium salt may be 3: 1: 1.

[0037] In the present invention, the usage ratio of the organic ligand to the first organic solvent is preferably (1-5) mg:1 mL, more preferably 3 mg:1 mL. In an embodiment of the present invention, the usage ratio of the organic ligand to the first organic solvent may be 3 mg:1 mL.

[0038] In the present invention, the first mixing is preferably carried out under ultrasonic conditions, the frequency of the ultrasound is preferably 40 to 60 KHz, more preferably 50 KHz; the time is preferably 5 to 30 min, more preferably 15 min.

[0039] In the present invention, the temperature of the first solvent thermal reaction is preferably 80-250°C, more preferably 100-200°C; the time is preferably 12-72h, more preferably 40-50h. In an embodiment of the present invention, the temperature of the first solvent thermal reaction can be 150°C, and the time can be 48h.

[0040] After the first solvent thermal reaction is completed, the present invention also preferably includes cooling, centrifugation, washing and drying in sequence. The present invention does not have any special restrictions on the cooling process, and the cooling to room temperature can be performed using a process well known to those skilled in the art. In the present invention, the speed of the centrifugation is preferably 5000-20000rpm, more preferably 10000rpm; the time is preferably 2-10min, more preferably 5min. In an embodiment of the present invention, the speed of the centrifugation can be 10000rpm, and the time can be 5min. In the present invention, the washing is preferably repeated with DMF and anhydrous ethanol in sequence; the number of repetitions is preferably 2-5 times, more preferably 3 times. In the present invention, the drying temperature is preferably 50-100°C, more preferably 60-80°C; the time is preferably 12-72h, more preferably 40-50h. In an embodiment of the present invention, the drying temperature can be 80°C and the time can be 48h.

[0041] After obtaining the cerium-doped metal organic framework, the present invention secondly mixes the cerium-doped metal organic framework, carbon nanotubes and a second organic solvent, and then performs a second solvothermal reaction to obtain a carbon nanotube and cerium-doped metal organic framework composite.

[0042] In the present invention, the second organic solvent preferably includes one or more of N,N-dimethylformamide (DMF), dimethyl sulfoxide, acetonitrile and anhydrous ethanol. When the second organic solvent is two or more of the above specific selections, the present invention has no special restrictions on the ratio of the above specific substances, and they can be mixed in any ratio. In an embodiment of the present invention, the second organic solvent can be DMF.

[0043] In the present invention, the mass ratio of the cerium-doped metal organic framework to the carbon nanotubes is preferably (5-15):1, more preferably (8-12):1. In the present invention, the mass ratio of the cerium-doped metal organic framework to the carbon nanotubes may be 10:1.

[0044] In the present invention, the usage ratio of the cerium-doped metal organic framework to the second organic solvent is preferably (1-10) mg:1 mL, more preferably (1-5) mg:1 mL. In an embodiment of the present invention, the usage ratio of the cerium-doped metal organic framework to the second organic solvent can be 5 mg:1 mL.

[0045] In the present invention, the second mixing is preferably carried out under ultrasonic conditions, the frequency of the ultrasound is preferably 20 to 100 KHz, more preferably 80 KHz; the time is preferably 5 to 30 minutes, more preferably 15 minutes.

[0046] In the present invention, the temperature of the second solvent thermal reaction is preferably 70-200°C, more preferably 100-150°C; the time is preferably 12-72h, more preferably 40-50h. In an embodiment of the present invention, the temperature of the second solvent thermal reaction can be 150°C, and the time can be 48h.

[0047] After the second solvent thermal reaction is completed, the present invention also preferably includes cooling, centrifugation, washing and drying in sequence. The present invention does not have any special restrictions on the cooling process, and the cooling to room temperature can be performed using a process well known to those skilled in the art. In the present invention, the speed of the centrifugation is preferably 5000-20000rpm, more preferably 10000rpm; the time is preferably 2-10min, more preferably 5min. In an embodiment of the present invention, the speed of the centrifugation can be 10000rpm, and the time can be 5min. In the present invention, the washing is preferably repeated with DMF and anhydrous ethanol in sequence; the number of repetitions is preferably 2-10 times, more preferably 3 times. In the present invention, the drying is preferably vacuum drying; the temperature of the vacuum drying is preferably 60-100°C, more preferably 80°C; the time is preferably 4-20h, more preferably 12h. In an embodiment of the present invention, the temperature of the vacuum drying can be 80°C, and the time can be 12h.

[0048] After obtaining the carbon nanotube and cerium-doped metal organic framework composite, the present invention calcines the carbon nanotube and cerium-doped metal organic framework composite to obtain the adsorption material.

[0049] In the present invention, the calcination is preferably carried out in a protective atmosphere, and the protective atmosphere is preferably a nitrogen atmosphere or an argon atmosphere, and more preferably a nitrogen atmosphere. In an embodiment of the present invention, the protective atmosphere may be a nitrogen atmosphere. In the present invention, the calcination temperature is preferably 250 to 600°C, and more preferably 300 to 400°C; the heating rate is preferably 2 to 10°C / min, and more preferably 4 to 8°C / min, and the holding time is preferably 4 to 10h, and more preferably 6 to 8h. In an embodiment of the present invention, the calcination temperature may be 400°C, the heating rate may be 5°C / min, and the holding time may be 8h.

[0050] The present invention also provides an adsorption material prepared by the preparation method described in the above technical solution, comprising carbon nanotubes and a bimetallic center oxide material centered on iron and cerium loaded in the carbon nanotubes.

[0051] In the present invention, the carbon nanotubes are porous structures, and the porous structure is formed during the calcination process.

[0052] In the present invention, the mass ratio of the bimetallic center oxide material centered on iron and cerium to the porous carbon material is preferably (5-15):1, more preferably 10:1.

[0053] In the present invention, the mass ratio of the iron element to the cerium element in the bimetallic center oxide material centered on iron and cerium is preferably 1:1.

[0054] In the present invention, the specific surface area of ​​the bimetallic oxide material centered on iron and cerium is preferably 523.34 to 856.23 cm 2 / g, more preferably 856.23cm 2 The specific surface area of ​​the carbon nanotubes is preferably 52 to 500 cm 2 / g, more preferably 500cm 2 / g.

[0055] In the present invention, the specific surface area of ​​the adsorbent material is preferably 865.34 to 1123.23 cm 2 / g.

[0056] The present invention also provides application of the adsorption material described in the above technical solution in the field of arsenic removal from groundwater.

[0057] In the present invention, the application method preferably comprises: placing the adsorbent material in arsenic-containing groundwater, stirring and mixing, allowing the mixture to stand until solid-liquid separation occurs, and taking the supernatant to obtain groundwater after arsenic removal.

[0058] In the present invention, the concentration of arsenic in the arsenic-containing groundwater is preferably 0.03-0.1 mg / L.

[0059] In the present invention, the usage ratio of the adsorption material to the arsenic-containing groundwater is preferably (0.25-0.6) g:1 L, and more preferably (0.3-0.5) g:1 L.

[0060] The technical solutions in the present invention will be described clearly and completely below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0061] Example 1

[0062] 15 mol of trimesic acid, 5 mol of ferric chloride hexahydrate and 5 mol of cerium nitrate hexahydrate (the molar ratio of trimesic acid, ferric chloride hexahydrate and cerium nitrate hexahydrate is 3:1:1) were added to 2.1 mL of DMF, ultrasonically vibrated at a frequency of 50 MHz for 15 min until completely dissolved, and then solvothermally reacted at 150° C. for 48 h. The mixture was cooled to room temperature and centrifuged at a speed of 10,000 rpm for 5 min. After washing with DMF and anhydrous ethanol for 3 times, the obtained powder was dried at 80° C. for 12 h to obtain Fe / Ce-MOF-1 (black solid).

[0063] 500 mg of the Fe / Ce-MOF and 50 mg of carbon nanotubes were uniformly mixed in 100 mL of DMF, subjected to ultrasonic vibration at a frequency of 80 KHz for 15 min, subjected to solvothermal reaction at 150° C. for 48 h, cooled to room temperature, centrifuged at a speed of 10,000 rpm for 5 min, washed with DMF and anhydrous ethanol three times in sequence, and the obtained powder was vacuum dried at 80° C. for 12 h to obtain CNT-Fe / Ce-MOF-1;

[0064] 200 mg of the CNT-Fe / Ce-MOF-1 was calcined in a nitrogen atmosphere (the calcination temperature was 400°C, and the temperature was increased to the calcination temperature at a heating rate of 5°C / min for 8 hours) to obtain CNT-Fe / Ce-MOF / NC-1 (black solid, including carbon nanotubes (porous structure) and a bimetallic center oxide material centered on iron and cerium loaded in the carbon nanotubes, the mass ratio of the bimetallic center oxide material centered on iron and cerium to the porous carbon material is 10:1, and the mass ratio of iron element to cerium element in the bimetallic center oxide material centered on iron and cerium is 1:1).

[0065] Application Example 1

[0066] 3 g of the CNT-Fe / Ce-MOF / NC-1 described in Example 1 was added to 10 L of arsenic-containing groundwater, stirred at a speed of 30 rpm for 1 h, and allowed to stand for 0.5 h until the solid-liquid separation was complete. The supernatant was siphoned to obtain the groundwater after arsenic removal (the concentration of As ions in the groundwater after arsenic removal was determined by ICP method to be 0.001 mg / L);

[0067] The arsenic-containing groundwater comes from a domestic waste landfill in Ningxia, and its main components are shown in Table 1:

[0068] Table 1 Composition of arsenic-containing groundwater

[0069]

[0070]

[0071] It can be seen that the arsenic removal rate of the CNT-Fe / Ce-MOF / NC-1 is 97.5%.

[0072] Application Example 2

[0073] 6 g of the CNT-Fe / Ce-MOF / NC-1 described in Example 1 was added to 20 L of arsenic-containing groundwater, stirred at a speed of 30 rpm for 1.5 h, and allowed to stand for 0.5 h until the solid-liquid separation was complete. The supernatant was siphoned to obtain the groundwater after arsenic removal (the concentration of As ions in the groundwater after arsenic removal was determined by ICP method to be 0.001 mg / L);

[0074] The arsenic-containing groundwater comes from a domestic waste landfill in Ningxia, and its main components are shown in Table 2:

[0075] Table 2 Composition of arsenic-containing groundwater

[0076]

[0077] It can be seen that the arsenic removal rate of the CNT-Fe / Ce-MOF / NC-1 is 98.3%.

[0078] Example 2

[0079] 15 mol of trimesic acid, 5 mol of ferric citrate and 5 mol of cerium acetate were added to 2.2 mL of DMF, ultrasonically vibrated at a frequency of 50 MHz for 15 min until completely dissolved, and then solvothermally reacted at 150°C for 48 h. The mixture was cooled to room temperature, centrifuged at 10,000 rpm for 5 min, washed with DMF and anhydrous ethanol three times in sequence, and the obtained powder was dried at 80°C for 12 h to obtain Fe / Ce-MOF-2 (black solid).

[0080] 500 mg of the Fe / Ce-MOF-2 and 50 mg of carbon nanotubes were uniformly mixed in 100 mL of DMF, subjected to ultrasonic vibration at a frequency of 80 KHz for 15 min, subjected to solvothermal reaction at 150° C. for 48 h, cooled to room temperature, centrifuged at a speed of 10,000 rpm for 5 min, washed three times with DMF and anhydrous ethanol in turn, and the obtained powder was vacuum dried at 80° C. for 12 h to obtain CNT-Fe / Ce-MOF-2;

[0081] 200 mg of the CNT-Fe / Ce-MOF-2 was calcined in a nitrogen atmosphere (the calcination temperature was 400°C, and the temperature was increased to the calcination temperature at a heating rate of 5°C / min for 8 hours) to obtain CNT-Fe / Ce-MOF / NC-2 (black solid, including carbon nanotubes (porous structure) and a bimetallic center oxide material centered on iron and cerium loaded in the carbon nanotubes, the mass ratio of the bimetallic center oxide material centered on iron and cerium to the porous carbon material is 10:1, and the mass ratio of iron element to cerium element in the bimetallic center oxide material centered on iron and cerium is 1:1).

[0082] Application Example 3

[0083] 3 g of the CNT-Fe / Ce-MOF / NC-2 described in Example 2 was added to 10 L of arsenic-containing groundwater, stirred at a speed of 30 rpm for 1 h, and allowed to stand for 0.5 h until the solid-liquid separation was complete. The supernatant was siphoned to obtain the groundwater after arsenic removal (the concentration of As ions in the groundwater after arsenic removal was determined by ICP method to be 0.0014 mg / L);

[0084] The arsenic-containing groundwater comes from a domestic waste landfill in Ningxia, and its main components are shown in Table 3:

[0085] Table 3 Composition of arsenic-containing groundwater

[0086]

[0087] It can be seen that the arsenic removal rate of the CNT-Fe / Ce-MOF / NC-2 is 96.5%.

[0088] Application Example 4

[0089] 3 g of the CNT-Fe / Ce-MOF / NC-2 described in Example 1 was added to 10 L of arsenic-containing groundwater, stirred at a speed of 30 rpm for 1.5 h, and allowed to stand for 0.5 h until the solid-liquid separation was complete. The supernatant was siphoned to obtain the groundwater after arsenic removal (the concentration of As ions in the groundwater after arsenic removal was determined by ICP method to be 0.0019 mg / L);

[0090] The arsenic-containing groundwater comes from a domestic waste landfill in Ningxia, and its main components are shown in Table 4:

[0091] Table 4 Composition of arsenic-containing groundwater

[0092]

[0093] It can be seen that the arsenic removal rate of the CNT-Fe / Ce-MOF / NC-2 is 96.8%.

[0094] Example 3

[0095] 15 mol of 2-aminobenzoic acid, 5 mol of ferric chloride hexahydrate and 5 mol of cerium nitrate hexahydrate were added to 2 mL of DMF, ultrasonically vibrated at a frequency of 50 MHz for 15 min until completely dissolved, and then solvothermally reacted at 150 ° C for 48 h. The mixture was cooled to room temperature and centrifuged at a speed of 10000 rpm for 5 min. After washing with DMF and anhydrous ethanol for 3 times, the obtained powder was dried at 80 ° C for 12 h to obtain Fe / Ce-MOF-3 (black solid).

[0096] 500 mg of the Fe / Ce-MOF-3 and 50 mg of carbon nanotubes were uniformly mixed in 100 mL of DMF, subjected to ultrasonic vibration at a frequency of 80 KHz for 15 min, subjected to solvothermal reaction at 150° C. for 48 h, cooled to room temperature, centrifuged at a speed of 10,000 rpm for 5 min, washed with DMF and anhydrous ethanol three times in sequence, and the obtained powder was vacuum dried at 80° C. for 12 h to obtain CNT-Fe / Ce-MOF-3;

[0097] 200 mg of the CNT-Fe / Ce-MOF-3 was calcined in a nitrogen atmosphere (the calcination temperature was 400°C, and the temperature was increased to the calcination temperature at a heating rate of 5°C / min for 8 hours) to obtain CNT-Fe / Ce-MOF / NC-3 (black solid, including carbon nanotubes (porous structure) and a bimetallic center oxide material centered on iron and cerium loaded in the carbon nanotubes, the mass ratio of the bimetallic center oxide material centered on iron and cerium to the porous carbon material is 10:1, and the mass ratio of iron element to cerium element in the bimetallic center oxide material centered on iron and cerium is 1:1).

[0098] Application Example 5

[0099] 3 g of the CNT-Fe / Ce-MOF / NC-3 described in Example 1 was added to 10 L of arsenic-containing groundwater, stirred at a speed of 30 rpm for 1 h, and allowed to stand for 0.5 h until the solid-liquid separation was complete. The supernatant was siphoned to obtain the groundwater after arsenic removal (the concentration of As ions in the groundwater after arsenic removal was determined by ICP method to be 0.0016 mg / L);

[0100] The arsenic-containing groundwater comes from a domestic waste landfill in Ningxia, and its main components are shown in Table 5:

[0101] Table 5 Composition of arsenic-containing groundwater

[0102]

[0103] It can be seen that the arsenic removal rate of the CNT-Fe / Ce-MOF / NC-3 is 96%.

[0104] Application Example 6

[0105] 3 g of the CNT-Fe / Ce-MOF / NC-3 described in Example 1 was added to 10 L of arsenic-containing groundwater, stirred at a speed of 30 rpm for 1.5 h, and allowed to stand for 0.5 h until the solid-liquid separation was complete. The supernatant was siphoned to obtain the groundwater after arsenic removal (the concentration of As ions in the groundwater after arsenic removal was determined by ICP method to be 0.0014 mg / L);

[0106] The arsenic-containing groundwater comes from a domestic waste landfill in Ningxia, and its main components are shown in Table 6:

[0107] Table 6 Composition of arsenic-containing groundwater

[0108]

[0109]

[0110] It can be seen that the arsenic removal rate of the CNT-Fe / Ce-MOF / NC-3 is 97.6%.

[0111] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications should also be regarded as the protection scope of the present invention.

Claims

1. A method for preparing an adsorbent material, characterized in that: The following steps are involved: After first mixing the organic ligand, the soluble iron salt, the soluble cerium salt and the first organic solvent, glacial acetic acid is added to perform a first solvothermal reaction to obtain a cerium-doped metal organic framework; After a second mixing of the cerium-doped metal organic framework, the carbon nanotubes and the second organic solvent, a second solvothermal reaction is performed to obtain a carbon nanotube and cerium-doped metal organic framework composite; The carbon nanotube and cerium-doped metal organic framework composite are calcined to obtain the adsorption material.

2. The preparation method according to claim 1, characterized in that The organic ligand includes one or more of trimesic acid, terephthalic acid and 2-aminoterephthalic acid.

3. The preparation method according to claim 1 or 2, characterized in that: The molar ratio of the organic ligand, the iron in the soluble iron salt and the cerium in the soluble cerium salt is (2-4):1:

1.

4. The preparation method according to claim 3, characterized in that: The temperature of the first solvent thermal reaction is 80-250° C. and the time is 12-72 hours.

5. The preparation method according to claim 1 or 4, characterized in that: After the first solvent thermal reaction is completed, the steps further include cooling, centrifugation, washing and drying.

6. The preparation method according to claim 1, characterized in that: The mass ratio of the cerium-doped metal organic framework to the carbon nanotube is (5-15):

1.

7. The preparation method according to claim 1 or 6, characterized in that: The temperature of the second solvent thermal reaction is 70-200° C. and the time is 12-72 hours.

8. The preparation method according to claim 1, characterized in that: The calcination is carried out in a protective atmosphere; The calcination temperature is 250-600° C., the heating rate is 2-10° C. / min, and the heat preservation time is 4-10 hours.

9. The adsorbent material prepared by the preparation method according to any one of claims 1 to 8, characterized in that: The invention comprises carbon nanotubes and a bimetallic center oxide material centered on iron and cerium and loaded in the carbon nanotubes.

10. Use of the adsorption material according to claim 9 in the field of arsenic removal from groundwater.